2015
DOI: 10.1542/peds.2014-1738
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate and the Risk of Trauma

Abstract: BACKGROUND AND OBJECTIVE: Children and adolescents with attention-deficit/hyperactivity disorder (ADHD) are prone to sustaining trauma that requires emergency department (ED) admission. Methylphenidate (MPH) can reduce ADHD symptoms and may thus theoretically reduce the risk of trauma-related ED admission, but previous studies do not make this association clear. This study examines this association.METHODS: A total of 17 381 patients aged 6 to 19 years who received MPH prescriptions were identified by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 95 publications
(108 citation statements)
references
References 37 publications
2
104
0
2
Order By: Relevance
“…13 CDARS has been used for conducting high-quality, population-based studies. [13][14][15][16][17] A local study showed high coding accuracy in CDARS with a positive predictive value (PPV) of 90%. 18 Nonetheless, we conducted further validation on a sample of patients in this cohort to ensure the validity of our data set.…”
Section: Data Sourcementioning
confidence: 99%
“…13 CDARS has been used for conducting high-quality, population-based studies. [13][14][15][16][17] A local study showed high coding accuracy in CDARS with a positive predictive value (PPV) of 90%. 18 Nonetheless, we conducted further validation on a sample of patients in this cohort to ensure the validity of our data set.…”
Section: Data Sourcementioning
confidence: 99%
“…The number of jobs in a given time period is increased as well as the rate of separations and divorces. Also, the risk for traumatic injuries is much higher than in general population (Man et al 2015). ADHD also increases the risk for violations of road traffic rules like speeding, driving after consumption of alcohol, driving without licence and the prevalence of traffic accidents (Jerome et al 2006;Vaa 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Since long-term randomized trials are impossible and unavailable due to ethical limitations, recent analyses from registries provide the most convincing evidence on the long-term benefits of methylphenidate. These studies indicate, for example, that treatment with methylphenidate has beneficial effects in terms of important distal outcomes that go beyond symptom control such as a reduction in comorbid depression, substance-use and dependency, trauma-related visits to the emergency room and mortality (Chang et al 2014(Chang et al , 2016Dalsgaard et al 2015;Man et al 2015). Furthermore, in the absence of clinically relevant effects of non-pharmacological treatment options on the core symptoms of ADHD (SonugaBarke et al 2013), a dogmatically biased devaluation of the currently most effective treatment is neither helpful for science nor patients.…”
Section: Resultsmentioning
confidence: 99%